Diagnosis and treatment of venous thromboembolism by consultants in Scotland. Issue 6342 (28th August 1982) - Prentice, A G; Lowe, G D; Forbes, C D
Abstract : A questionnaire was sent to 508 consultants in Scotland likely to encounter deep vein thrombosis and pulmonary embolism to assess their current standard practice in diagnosis and treatment of these disorders. Replies were received from 358 (70.5%). In deep vein thrombosis 47% and in pulmonary embolism 33% of consultants usually depended on clinical observation alone for diagnosis. In deep vein thrombosis 37% used venography to supplement clinical diagnosis and in pulmonary embolism 13% used angiography and 53% used isotopic scanning. Almost all consultants treated deep vein thrombosis (95%) and pulmonary embolism (99%) with anticoagulants. Most consultants (81%) gave heparin by intravenous infusion. Although many consultants gave intravenous heparin for more than three days (49.5% in deep vein thrombosis and 61% in pulmonary embolism), 25% of these consultants did not use any laboratory monitoring of heparin's effect. Large numbers of consultants gave warfarin for more than three months (20% in deep vein thrombosis and 47% in pulmonary embolism). There was a significant tendency to give heparin (p less than 0.01) and warfarin (p less than 0.001) for longer periods in pulmonary embolism than in deep vein thrombosis. This survey shows a widely varying practice and underlines the need for further controlled studies to provide clear guidance in the management of deep vein thrombosis and pulmonary embolism.